The literary paradigm and the discourses of culture: Contexts of Canadian writing, 1759-1867. - Walker, Victoria Jane. (University of Ottawa (Canada), 1997)
This study is of pre-Confederation writing from 1759-1867, and constitutes a reflection on the beginnings of the emergence of an autonomous literary institution in Canada. It deals with the grounding of the literary institution, and with questions related to the creation and emergence of national literatures. It does not attempt a totalizing examination of writing done during this vast time frame, but discusses, in a number of synchronic "case studies," some significant moments in the literary life of the colony. Each chapter dislocates the focus that is typically directed at a handful of disparate instances at the expense of other activities related to the practices of reading and writing, and of lesser-known writers who worked in less "literary" forms, and is intended to reorient our perception of some "canonical" writers of this period. In so doing, it questions some of the organizing frameworks that have been applied to Canadian literature, and proposes a broader conception of the literature of this period, especially since the literary field was only just beginning to define itself in the colony. An introductory section provides a discussion of some of the critical discourses that shaped the study of Canadian literature from the moment of its full institutionalization, in the 1960s and 1970s, and onwards. The second part of the opening section points out some of the consequences of these critical discourses for the conception of a Canadian national literature, and relates them to some earlier formulations of Canada's literary history. The first of the "case studies" is devoted to Frances Brooke and the reception in Canada of The History of Emily Montague (1769). The second chapter focuses on Thomas Cary and attempts to situate him not only as the author of one of the earliest poems printed in the colony, but also as editor of the Quebec Mercury. In this capacity he played a role in the early practices of reading and writing in the colony, and contributed to the largely political public discourse of his time. Chapter Three builds on this discussion by dealing with questions of identity and political allegiance as articulated in some early writings of Upper Canada. It starts out by examining the case of Julia Catherine Beckwith Hart and why Canadian critics have focused on one of her novels in particular, then proceeds to consider the uses that Bishop Strachan and politician Barnabas Bidwell made of writing and printing to sway public opinion and foster competing conceptions of identity. The fourth chapter looks at the role Canadian critics have assigned John Richardson. The concluding chapter, on Thomas D'Arcy McGee, reconsiders the role he is commonly seen to have played as a "father" of Canadian literature and visionary of a "new northern nationality." McGee's poetic figuring of Canada's past in the Canadian Ballads, and Occasional Verses (1858) was followed in subsequent writings by a dismissal of historical concerns in the name of an identity that was to be a thing of the future. The methodological approach suited to this endeavour is that suggested by literary systems theory, since it allows us to take into consideration the complex of factors or "interactions" that give rise to the practices of "literature."
Keywords: Literature, Canadian (English).